School Reform through Instructional Support The Pennsylvania Initiative. Part I: The Instructional Support Team (IST) [and] Part II: Instructional Evaluation - Kovaleski, Joseph F.; Tucker, James A.; Duffy, Daniel J., Jr.; Lowery, Paul E.; Gickling, Edward E. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
The document features two articles on school reform in Pennsylvania. Part one discusses the Instruction Support Team (IST) (Kovaleski, Tucker, and Duffy). The IST process is an intensive building-based pre-referral intervention program to assist elementary students experiencing difficulty in the classroom. The IST is a working group of teachers and other school professionals that helps teachers find solutions to instructional challenges through classroom-based assessment and collaborative problem-solving. Over a 5-year phase-in period, all 501 Pennsylvania school districts have initiated the IST program. Training is provided at the school level by IST Project consultants who assist team members in the design, planning, and implementation of the program. The components of the training are: collaboration and team building, instructional assessment, instructional adaptation, student discipline, and student assistance for at-risk issues. Each school's implementation of the IST process is evaluated by validation teams. In the initial phases of the project, an average of 50,000 elementary school students have been assisted by the IST process annually. Referrals for multidisciplinary evaluation and placements in special education have been reduced substantially in schools enrolled in the IST process. Part two discusses instructional evaluation (Kovaleski, Lowery, and Gickling). Instructional evaluation is a procedure in which a student's need for special education is systematically examined through an analysis of the student's responses to classroom-based interventions. The multidisciplinary team (MDT) uses the instructional evaluation process to analyze the level and intensity of the intervention(s) needed in order for the student to succeed in the regular education setting, or whether special education may be required. The MDT gathers the data necessary for making eligibility decisions and for design of an IEP for eligible students. A re-evaluation process reviews the student's IEP, determines which instructional approaches and techniques have been successful, and recommends changes to the IEP. (Contains 22 references.) (ND)
Sponsoring Agency: Pennsylvania State Dept. of Education, Harrisburg.
ERIC Note: For related IST documents, see SP 037 535-545.
Communique, v23 n8 Jun 1995 v24 n2 Oct 1995.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Change; Elementary Education; Elementary School Teachers; Inclusive Schools; Instructional Improvement; Models; Partnerships in Education; Special Education; Special Needs Students; State Programs; Team Training; Teamwork; Instructional Support; Pennsylvania; Journal Articles; Reports, Descriptive